Climate limit-indexes for the acerola crop growth - Teixeira, Antônio Heriberto de Castro; Azevedo, Pedro Vieira de (Pesquisa Agropecuaria Brasileira, 1995)
Based on the climatic water balance data, according to the method of Thornthwaite and Mather (1955), for a 125 mm soil moisture capacity, from both the region of natural dispersion and areas of commertial production of the acerola (Malpighia glabra L.) crop, climate limit-indexes for the crop growth were defined. As a thermal factor for an optimum crop development and productivity, it was considered a temperature between 25oC and 27oC, with the plant being able to be commertially grown in regions with annual average temperature equal or greater than 20oC and an average temperature in the coldest month around 14oC. Once the thermal requirements are satisfied, a higher water availability provides a higher ascorbic acid content in the fruits, up to a limit above which the water excess is harmful. This humidity upper limit was established as 2,000 mm of annual rainfall in the regions of natural dispersion, corresponding to an annual hydric index (Hi) or an annual hydric excess (He) of 55 and 800 mm, respectively. Otherwise, the lower humidity limit was established as 1,200 mm, corresponding to an annual hydric index or an annual hydric deficiency (Hd) of - 15 and 400 mm, respectively.